The dinosaur disaster - McElligott, Matthew (McElligott, Matthew. Mad Scientist Academy., 2015)
"Dr. Cosmic's class of clever monsters at the Mad Scientist Academy solve the greatest challenges in science, in this perfect blend of adventure and exploration." --